The distribution of glacial meltwater routes and associated murtoo fields in Finland - Ahokangas Elina; Ojala Antti E.K.; Tuunainen Aleksi; Valkama Markus; Palmu Jukka-Pekka; Kajuutti Kari; Mäkinen Joni (Elsevier B.V., 2022)
Abstract
High-resolution LiDAR (Light detection and Ranging) -based digital elevation models (DEM) have greatly improved the mapping of glacial landforms and revealed new ones such as murtoos. Murtoos have extensive diversity in form, relief and size, and they often appear along meltwater routes. However, not all meltwater routes in the recently glaciated terrains include murtoos. We mapped different types of subglacial meltwater routes and the related distribution of murtoos in the Finnish part of Fennoscandian Ice Sheet (FIS). Subglacial meltwater routes represent a previously unknown extension of the subglacial hydrological system that supplements esker networks. Murtoo deposition along the routes is dictated by the marked concentration and routing of subglacial meltwater in a high-pressure environment outside the subglacial tunnel flow and channelized drainage zone. The main environments of murtoo route genesis include the margins of glacial lineation fields, lateral shear margins of ice streams or in between ice-flow sectors or corridors, confluence zones of ice stream onset areas, lee-sides of bedrock protrusions or thresholds, bedrock fracture valleys and potential subglacial lake inputs and outputs. This study adds to the knowledge of the development of subglacial drainage and emphasizes the role of murtoos as the potential missing link between the channelized and distributed subglacial drainage.